Lessons learned from economic crisis? Environmental and ecological economics in the Czech Republic - Vávra, Jan (Jihočeská univerzita v Českých Budějovicích, Ekonomická fakulta, 2013)
This essay tries to describe the present state of environmental and ecological economics among the economic scholars from the Czech Republic. It is based on the assumption, that recent financial, debt and economic crisis was an opportunity to change the current growth paradigm. Brief introduction covering the history of the concept of sustainable development and current trends like ?green? or ?sustainable? growth is presented as well as selected moments from the recent Czech politics and economy. More attention is paid to the academic economics dealing with environmental issues. The results show that some academic departments employ the concept of environmental and resource economics, but only few scholars are interested in the ecological economics and critically assess the context of growth. The crisis obviously did not help to change the growth paradigm in the Czech academia, neither in the Czech politics. Wider variety of economic viewpoints towards the social, economic and environmental challenges could help to understand them more and to find better solutions.
Co jsme si odnesli z ekonomické krize? Environmentální a ekologická ekonomie v České republice
Keywords: environment; growth; sustainable development; Czech Republic; environmental economics; ecological economics; životní prostředí; udržitelný rozvoj; Česká republika; environmentální ekonomie; ekologická ekonomie